Factors Associated With Healthcare Workers' Insomnia Symptoms and Fatigue in the Fight Against COVID-19, and the Role of Organizational Support - Zou, Xia; Liu, Shaokun; Li, Jie; Chen, Wen; Ye, Jiali; Yang, Yuan; Zhou, Fenfen; Ling, Li (Frontiers in Psychiatry, 2021)
Background: Healthcare workers (HCWs) have been exposed to increased risks of insomnia and fatigue during the COVID-19 pandemic. In this study, we identify important risk factors associated with insomnia symptoms and fatigue among HCWs, and evaluate the effect of organizational support on insomnia and fatigue symptoms. Methods: This is an online cross-sectional survey of HCWs in China administered during the COVID-19 epidemic (from February 27, 2020 to March 12, 2020). We employed the AIS-8 scale for insomnia screening, and a self-reported ten-point scale to evaluate subjects' degrees of fatigue. We also designed a four-point scale to assess the degree of social support provided on an organizational level. Additionally, we conducted logistic regression analysis to identify risk factors. Results: This study included a total of 3,557 participants, 41% of which consisted of non-frontline HCWs and 59% of which was frontline HCWs. Of the non-frontline HCWs, 49% reported insomnia symptoms, and 53.8% reported a moderate to high degree of fatigue. Meanwhile, among the frontline HCWs, the percentages for insomnia and moderate to high fatigue were 63.4% and 72.2%, respectively. Additionally, frontline HCWs and HCWs employed at Centers for Disease Control and Prevention (CDCs) had elevated risks of insomnia and fatigue. However, with increased organizational support, insomnia symptoms decreased among frontline HCWs. Also, organizational support mitigated the positive correlation between daily working hours and degree of fatigue among HCWs. Conclusion: Frontline HCWs and staff in Chinese CDCs have been at a high risk of insomnia symptoms and fatigue during the fight against COVID-19. This study provides evidence for the positive effects of organizational support in relation to insomnia and fatigue among HCWs. This sheds light on government responses to the COVID-19 epidemic for other countries.